Changes in heart period during endodontic treatment - Santana, Milana D R; Sousa, Ana CecÍlia Amorim De; Assis, Elisangela Vilar de; Abreu, Luiz Carlos de; Valenti, Vitor Engrácia [UNESP] (My University, 2014)
Background: Tooh extraction was demonstrated to increase sympathetic modulation of the heart, however, it is not understood the effects of endodontic treatment on cardiac autonomic regulation. We evaluated heart rate variability (HRV) during endodontic treatment. Method: 50 male and female patients aged between 18 and 40 years old and diagnosed with irreversible pulpitis or pulp necrosis of the lower molars with indication of gender endodontic treatment were analyzed. HRV was analyzed in the time (SDNN, RMSSD, pNN50) and frequency (LF, HF and LF/HF ratio) domains recorded in the first session of root canal treatment. The indices were analyzed in the following periods: T1) ten minutes before the endodontic treatment, T2) ten minutes after the administration of anesthesia before endodontic treatment, T3) during the entire period of endodontic treatment and T4) thirty minutes after the end of the endodontic treatment. Results: The SDNN, RMSSD and pNN50 indices increased at T2 compared to T1, the pNN50 and RMSSD indices increased at T3 and T4 compared to T2. The LF in normalized units increased at T4 compared to T2 and in absolute units it was increased at T4 compared to T1. The HF in normalized units was reduced at T4 compared to T2 and in absolute units was reduced at T1, T3 and T4 compared to T2. The LF/HF ratio was higher at T4 compared to T2. Conclusion: The global modulation of heart increases after local anesthesia and vagal tone reduce during surgery procedures and after the surgical procedures.